2010
DOI: 10.1097/phh.0b013e3181dfbb72
|View full text |Cite
|
Sign up to set email alerts
|

Housing Interventions at the Neighborhood Level and Health

Abstract: A panel of subject matter experts systematically reviewed evidence linking neighborhood-level housing interventions, such as housing programs or policies, to health outcomes. One of the 10 interventions reviewed--the Housing Choice Voucher Program--had sufficient evidence for implementation or expansion. The evidence showed that voucher holders are less likely to suffer from overcrowding, malnutrition due to food insecurity, and concentrated neighborhood poverty than non-voucher holders. Of the other reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Chicago is the most frequently studied city (Keene & Geronimus, 2011;Kling et al, 2005;Lindberg et al, 2010;Popkin et al, 2009Popkin et al, , 2012Sharkey & Sampson, 2010), while MTO and HOPE VI are the most frequently studied housing policies (Table 2). Table 2 shows the terms we used to how each paper measured violence-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chicago is the most frequently studied city (Keene & Geronimus, 2011;Kling et al, 2005;Lindberg et al, 2010;Popkin et al, 2009Popkin et al, , 2012Sharkey & Sampson, 2010), while MTO and HOPE VI are the most frequently studied housing policies (Table 2). Table 2 shows the terms we used to how each paper measured violence-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lindberg et al found that perceived safety among participants in 17 focused on gentrification but did not address violence and crime trends as correlates of relocation 5 focused on socioeconomic indicators associated with urban renewal, or on qualitative changes since relocating, but not on changes in crime or violence as a result of displacement 3 focused on racial identity and activism against redevelopment 2 referred only to origin neighborhoods 1 focused on crime generally but did not make specific references to violence 1 focused on social inclusion 1 focused on racial integration 1 focused primarily on housing as a human right 1 focused on the legality of eviction 1 non-U.S. based 1 citation a photo essay Public housing AND transition AND crime 2 1 (Cummings, DiPasquale, & Kahn, 2002) 1 focused on emancipation of foster children Casas et al 3 Table 2. MTO improved among 85% in the experimental group, 71% in the geographically unrestricted Section 8 group, and 55% of those in the control group (Lindberg et al, 2010). Literature assessing HOPE VI and its impact on specific violence-related outcomes in destination neighborhoods is much larger.…”
Section: Housing Policy and Mobility Patternsmentioning
confidence: 95%
“…6 Characteristics of neighborhoods have also been associated with health, mental health, and behavioral outcomes. 7 Relationships have been shown between a higher density of alcohol establishments in urban neighborhoods and rates of four types of violent crime, 8 between noise, overcrowding, absence of green space, community facilities, and fear of crime with lower mental health status and vitality scores, 9 and between neighborhoods defined in various ways as being disadvantaged and higher levels of depression and psychiatric distress. [10][11][12] While this accumulation of evidence makes it clear that housing and neighborhood quality are important social and physical ecological variables that may mediate or moderate outcomes in housing intervention research, Bobjective^housing and/or neighborhood quality is rarely measured in studies of housing interventions for homeless individuals including those with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…9 Similarly, both single and composite characteristics of neighborhoods have been associated with health, mental health, and behavioral outcomes. 10 For example, Toomey et al documented relationships between a higher density of alcohol establishments in urban neighborhoods and rates of four types of violent crime. 11 Guite et al linked specific aspects of the physical and urban environment in London (including noise, overcrowding, absence of green space, community facilities, and fear of crime) with lower mental health status and vitality scores 12 in the general population.…”
Section: Background and Rationalementioning
confidence: 99%